2019
DOI: 10.3390/ijms20163954
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and Bactericidal Mechanism of Histidine-Rich β-Hairpin Peptide Against Gram-Negative Bacteria

Abstract: Antibacterial peptides (APMs) are a new type of antibacterial substance. The relationship between their structure and function remains indistinct; in particular, there is a lack of a definitive and fixed template for designing new antimicrobial peptides. Previous studies have shown that porcine Protegrin-1 (PG-1) exhibits considerable antimicrobial activity and cytotoxicity. In this study, to reduce cytotoxicity and increase cell selectivity, we designed histidine-rich peptides based on the sequence template R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 51 publications
1
46
0
Order By: Relevance
“…The results of MICs indicated that the designed peptides had good antibacterial activity toward Gram-negative bacteria ( Table 2). Compared to the single membrane and thick peptidoglycan layer of Gram-positive bacteria, the double-membrane structure of Gram-negative bacteria represents a weaker barrier; thus, Gram-negative bacteria are more sensitive to AMPs [17,21,24]. The antibacterial activity of AMPs can be affected by many factors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of MICs indicated that the designed peptides had good antibacterial activity toward Gram-negative bacteria ( Table 2). Compared to the single membrane and thick peptidoglycan layer of Gram-positive bacteria, the double-membrane structure of Gram-negative bacteria represents a weaker barrier; thus, Gram-negative bacteria are more sensitive to AMPs [17,21,24]. The antibacterial activity of AMPs can be affected by many factors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that cationic AMPs combine with anions on the surface of bacteria via electrostatic action, and their hydrophobic amino acids are inserted into the bacterial cell membrane. Once the critical concentration is exceeded, the membrane breaks, and this ultimately leads to death of the bacteria [21,22]. LR pG firstly bound to the LPS of the outer membrane of E. coli ATCC25922 through electrostatic action (Figure 8), and then destroyed the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations